2021
DOI: 10.3390/ijerph18179418
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Frequency of Physical Activity in Spanish Students Aged 8–14

Abstract: The study of health-related quality of life (HRQoL) in children and adolescents has important implications in terms of policy, education, and health. Data on the time spent in physical activity (PA) and in sedentary activities in this population are worrying. We aim to analyze possible differences in HRQoL and PA levels between sexes and age groups in Spanish students aged between 8 and 14 years, as well as to assess the relationship between HRQoL and the frequency of PA in this population. A total of 3197 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
1
7
0
1
Order By: Relevance
“…PA implemented with a low, moderate and/or vigorous intensity is essential to encourage health promotion. High-intensity PA is related to greater physical tness, bone health, motor skills [39]. Our ndings are consistent with previous studies during the pandemic, suggesting that higher MVPA levels are associated with reduced depressive, anxiety symptoms [43][44][45][46]..…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PA implemented with a low, moderate and/or vigorous intensity is essential to encourage health promotion. High-intensity PA is related to greater physical tness, bone health, motor skills [39]. Our ndings are consistent with previous studies during the pandemic, suggesting that higher MVPA levels are associated with reduced depressive, anxiety symptoms [43][44][45][46]..…”
Section: Discussionsupporting
confidence: 91%
“…Overall, HRQoL seems to improve as students are included in higher PA levels [39].These results were in line with previous studies [39][40][41]. statistically signi cant differences in HRQoL are reported between students who do not engage in any kind of exercise/physical activity or do it irregularly and those who do it several times a week [39].Wu et al [40].suggested that elevated levels of physical activity are associated with higher PedsQL, whereas a low level of PA and higher time spent in sedentary behavior are inversely related to health-related quality of life among children and adolescents. Masini et al [41].showed that Children who spent more time partaking in moderate PA were associated with a higher total PedsQL score.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies focus on the relationship between PA and HRQOL, but most have concentrated on specific age groups, such as children ( 3 ), adolescents ( 22 ), students ( 23 ), middle-age population, or older adult population ( 24 28 ). The conclusions drawn from these studies consistently indicated that higher PA levels are associated with better HRQOL ( 3 , 23 , 29 ). Previous research on HRQOL among older adult populations has shown that the oldest adults reported worse HRQOL than the younger older adult individuals ( 21 , 30 ).…”
Section: Introductionmentioning
confidence: 72%
“…En los últimos años se han presentado varios estudios que analizan los beneficios de AF en la fase escolar tanto en niños y adolescentes (Calzada-Rodríguez et al, 2021;Matsudo, 2012;Sánchez-López et al, 2009) sobre las funciones ejecutivas (van der Niet et al, 2015;Visier-Alfonso et la., 2021), tambien cómo afecta la CS a las FE tanto en hombres como en mujeres (Patraca-Camacho et al, 2022). El presente estudio nace ante la creciente incertidumbre de la influencia de las CS en el desarrollo de la población infantil durante el confinamiento dentro del contexto de pandemia, el cual obligó a modificar las metodologías presenciales en toda actividad practicada, cambiando el ritmo de trabajo y disminuyendo los estímulos y las experiencias otorgadas a los estudiantes para su proceso de aprendizaje y desarrollo dentro de todos los ámbitos posibles (Castillo et al, 2021).…”
Section: Introductionunclassified